Pengembangan Media Flashcard Berbasis Nilai Keteladanan Nabi Muhammad SAW Pada Materi Sistem Eksresi Kelas XI - Azlina, Putri Aprilia; Rahmadina (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop flashcard learning media based on the exemplary values ​​of the Prophet Muhammad SAW on the excretory system material for grade XI as a solution to these problems. This study used the 4D development model (Define, Design, Develop, Disseminate) with subjects such as teachers and grade XI students, and involved media experts, material experts, and hadith interpreters. Data in this study were collected through interviews with biology teachers and questionnaires to media experts, material experts, and hadith interpreters as well as practicality tests by teachers and students. The results of the study on media experts were 91.1% (very feasible), material experts 95% (very feasible), and hadith interpreters 88.64% (very feasible) with an average score of 91.58% (very feasible). The results of the practicality test on teachers obtained a score of 97.5% (very practical) and students obtained a score of 89.51% (very practical) with an average score of 93.3% (very practical). Thus, it can be concluded that the flashcard media based on the exemplary values ​​of the Prophet Muhammad SAW in the Excretory System material is declared valid and practical so that it can be used as a supporting medium for biology, especially in the excretory system material.